Analisis Upaya Guru Mengatasi Kesulitan Membaca pada Siswa Kelas 1 SDN 195 Palembang - Regowo, Naufal Nachief Rigo; Akhbar, M. Taheri; Dedy, Adrianus (Indonesian Research Journal on Education, 2022)
This study aims to find out how the teacher’s efforts to overcome reading difficulties in grade 1students at SDN 195 Palembang. This study uses a qualitative approach with a descriptive method.The subjects of this study were grade 1 teachers, parents of grade 1 stundents and grade 1 stundents. Data collection in this study used interview techniques, questionnaires, anddocumentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the result of the study, it can be concluded that the teacher’s efforts to overcome reading difficulties for grade 1 stundents are the teacher providing advice, additional tutoring, and using learning media such as letter picture books using the lecturemethod so that students are motivated.